Popularização da ciência na revista Nova Escola: a comodificação do discurso sobre ensino de inglês - Bevilaqua, Raquel (2015)
This research was developed as part of the CNPq projects Análise crítica de gêneros com foco em artigos de popularização da ciência (MOTTA-ROTH, 2007), and Análise crítica de gêneros discursivos em práticas sociais de popularização da ciência (MOTTA-ROTH, 2010) concerning the critical analysis of science popularization genre. The science popularization (SP) involves a complex process of recontextualization of the scientific discourse in the mass media, which is realized in different discourse genres, such as SP news and reportage (MOTTA-ROTH, 2009). In this process, the journalist mediator appropriates and re-elaborates the knowledge produced by specialists to non-specialized audience by making use of different linguistic strategies, such as reformulation (HYLAND; 2007; LOVATO, 2010; GERHARDT, 2011). The objective of this study is to analyze the popularization process of the discourse about English language teaching in didactic reportages published on Nova Escola online by considering the reformulation strategies. In order to conduct this investigation, two corpora were selected: academic articles on language teaching and learning, published at Brazilian leading journals of Applied Linguistics, whose objective was to identify the contemporary conversations (GEE, 2001) about the issue; and didactic reportages about English language teaching, published on Nova Escola online. The analysis concerning the first corpus indicated three recurrent conversations: Critical perspective; Multiliteracies; Discourse genre, which suggest a critical linguistic education practice based on the use of language as a complex sociosemiotic system, as well as on the role of the school teacher conceived as an agent of critical (multi)literacies. The analysis of the second corpus indicated divergence from the contemporary conversations regarding two main aspects: language is conceived as lexicogrammar, and the teacher is positioned as a consumer of how-to recipes. The theoretical and methodological perspective adopted in this study is Critical Genre Analysis (MEURER, 2001; MOTTA-ROTH, 2008), an interdisciplinary perspective formed by Critical Discourse Analysis (FAIRCLOUGH, 2003, 2001), Socio-rhetoric (MILLER, 1984, SWALES, 2004; BAZERMAN, 2005) and Systemic Functional Linguistics (HALLIDAY; HASAN, 1989; HALLIDAY; MATTHIESSEN, 2004).